Teoria do processo eleitoral democrático: a formação dos mandatos a partir da perspectiva da cidadania - Roberta Maia Gresta (2019)
This thesis proposes to theorize the democratic electoral process as the axis of connection between Political Law, Electoral Law and Procedural Law. The problem-situation is delineated from the observation that, although the expression electoral process appears in rule 16 of the Brazilian Constitution (CRFB) which indicates the constitutional option to elaborate it alongside the legislative, administrative and judicial process , so far it has not challenged studies under the approach of process theory. The problematization presupposes the normative context of the Democratic State of Law instituted in 1988, the inscription of due process of law in the constitutional text and the impossibility of discarding a priori the understanding of the electoral process as a linguistic sign that carries an epistemological and normative claim. The hypothesis raised is that the emptying of this claim and the reduction of the electoral process to an operational concept, notedly a timeframe, result from the view of the process as an instrument of state authority, which, although overcome by the democratic processuality paradigm, remains hegemonic in the literature and in case-law, and prevents, in particular, an adequate understanding of a procedural matrix whose singularity is to produce a public decision achieved by the exercise not of one of the functions of the State, but rather of the decisionmaking competence of the citizens. The general objective of the research is to propose a foundation for a theory of the democratic electoral process based on the understanding of the Constitution as a discourse that provides an intradiscursive code, composed by the constitutional statute of political rights, for the verdiction of the meanings (interpretations) attributed to the electoral process. The theoretical framework adopted is the conception of verdiction as intradiscursive confirmation (theory of the interpretant, by Edward Lopes) and process as a self-critical juridical-linguistic institution, which promotes the discursive equalization of the State and Citizenship and the leveling of subjects of law (neoinstitucionalist theory of the process, by Rosemiro Pereira Leal). The thesis defended is that the electoral process is the discursive space demarcated, by the institutional principles of the process and by the constitutional statute of political rights, for Citizenships performance in the concretization of democratic statehood, in which the legitimized to act exercise their decision-making competence of forming elective mandates, in an isomenic position with the State and with the other components of the juridical community. They are methodological aspects of the research: theoretical research; interdisciplinary character; line of critical-methodological research; juridical-theoretical aspect, as demarcated in popperian epistemology; hypothetical-deductive reasoning; juridical-interpretative research with a propositional character. As a procedure (and not an autonomous strategy apt to characterize this research as empirical), a case study will be carried out. It will be taken as primary data the decisions of the Full Court of STF, which, within the timeframe of post-1988, addresses the question of the application of the electoral annuity rule (art. 16, CRFB), which would require, by hermeneutical hypothesis, to state a conception of electoral process, having as a temporal cut the period after the Constitution of 1988.